Effect of Mangosteen Pericarp Extract on Gastric Mucosal Damage Induced by Aspirin - Budiono, Jansen; Achadiyani, Achadiyani; Girawan, Dolvy (Althea Medical Journal, 2016)
Background: Peptic ulcer disease is commonly found in the community. Nonsteroidal anti-inflammatory drug (NSAID) such as aspirin is one of the predisposing factors to ulcers. According to various studies, plant extracts have been shown to produce promising results in the treatment of peptic ulcers. Xanthone, the active substance contained in the mangosteen pericarp extract has been extensively studied for its role in various diseases. The present study was undertaken to identify the effect of mangosteen pericarp extract on gastric mucosal damage.Methods: This study was carried out from SeptemberâNovember 2014 in the Animal Laboratory of the Department of Pharmacology and Therapy, Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung. Thirty two rats were randomly divided into 2 groups with different treatments and were induced by aspirin. Histologic studies were conducted to determine the score of gastric mucosal damage. The parameters used were Wattimenaâs criteria for damage of gastric mucosa. Data was analyzed using Chi Square test and the outcome was measured in relative risk.Results: The study revealed a significant association between pretreatment with mangosteen pericarp extract and incidence of gastric mucosal damage induced by aspirin (p < 0.05). Calculation with a modified 2 Ã 2 table revealed a relative risk of 0.625.Conclusions: Rats pretreated with mangosteen pericarp extract exhibit less gastric mucosal damage, in experimentally aspirin-induced ulcer. [AMJ.2016;3(3):388â91]Â DOI: 10.15850/amj.v3n3.885